PEMBERIAN JUS SEMANGKA TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DI PANTI SOSIAL TRESNA WERDA ILOMATA KOTA GORONTALO - Rona Febriyona; Inne Ariane Gobel (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
The study was conducted on elderly patients whith hypertension at Tresna Werda Social House of Ilomata orontalo City, which aim to determing the effect of watermelon juice on blood pressure drop on elderly. The study design was Quasy experimental Pretes and Posttes by involving control groups. The sample of the research were 20 respondents divided into two groups: the experimental group were 10 respondets and the control groups were 10 respondents. Stastistical test analysis using paired t test. The result of statistic test in obtaining P value 0.000 less then a (P<0.05) which means HO is reected, so it can be conclded that there is influence of watermelon juice to blood preasure drop on elderly in social house Tresna Werda Social House of Ilomata Gorontalo City.